2022
DOI: 10.54905/disssi/v26i125/ms266e2203
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of irritable bowel syndrome and its association with academic performance in Umm Al-Qura University medical students

Abstract: Background: Irritable bowel syndrome (IBS) is one of the most prevalent global diseases and national health issues. IBS symptoms have an impact on a patient's quality of life as well as their capacity to work and study. Medical students are affected by IBS, but the rate of IBS is unknown. Accordingly, this study investigates the prevalence and impact of IBS among all medical students at the Umm Al-Qura University (UQU) Medical College. Methods: A cross-sectional study including all medical students at UQU. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…The student population was the leading group of this SR & MA based on 25 studies among the 38 studies with a pooled prevalence of 22% from 13,015 study participants. Two studies from the student group reported male predominance [11,44], similar to the findings of Japan, China, and South Korea [3]. However, most studies reported female predominance [15,25,27].…”
Section: Discussionsupporting
confidence: 68%
“…The student population was the leading group of this SR & MA based on 25 studies among the 38 studies with a pooled prevalence of 22% from 13,015 study participants. Two studies from the student group reported male predominance [11,44], similar to the findings of Japan, China, and South Korea [3]. However, most studies reported female predominance [15,25,27].…”
Section: Discussionsupporting
confidence: 68%